2022
DOI: 10.4081/jphia.2022.1937
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practices among healthcare workers regarding dengue in Togo

Abstract: In Togo where malaria is endemic, because main signs of malaria and dengue are similar, the use of malarial drugs first could contribute to a delay in the diagnosis of dengue and the dissemination of the disease. Thus, it is important that healthcare workers (HCW) have a good knowledge of these diseases. To assess the knowledge, and practices regarding dengue infection among HCW in Togo. A cross-sectional study was carried out from November 2020 to March 2021 among HCW in Togo. A pre-tested digital questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…This 2022 study in Kara, northern Togo, found that 49.1% of healthcare professionals had good knowledge of dengue fever, a figure similar to the 47.1% reported by Zida-compaoré et al in 2021 in Lomé, southern Togo ( 20 ). These results suggest a relatively low level of dengue knowledge among Togolese healthcare workers, lower than figures reported elsewhere.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…This 2022 study in Kara, northern Togo, found that 49.1% of healthcare professionals had good knowledge of dengue fever, a figure similar to the 47.1% reported by Zida-compaoré et al in 2021 in Lomé, southern Togo ( 20 ). These results suggest a relatively low level of dengue knowledge among Togolese healthcare workers, lower than figures reported elsewhere.…”
Section: Discussionsupporting
confidence: 62%
“…Healthcare professionals who were absent or on sick leave during the data collection period and those who refused to participate were excluded from the study. Based on the last study carried out in 2020 on the same subject which reported a proportion of good knowledge of 47.1% in Lomé of Togo, we assume a level of knowledge of 50 % on dengue, a margin of error of 5% and a confidence interval of 95%, the sample size was initially calculated as 384 ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was no standardized tool for assessment of knowledge for dengue among health care workers as well as facilities preparedness for dengue detection. To ensure content validity, the questionnaire development was informed by a review of World Health Organization guideline for clinical management of dengue [9], past survey of dengue knowledge among health care workers [22,23,37,[41][42][43][44][45][46][47][48][49], and other literature describing diagnostics and management of dengue [50][51][52][53][54]. Furthermore, a Cronbach Alpha coefficient was used to measure reliability and internal consistency (coefficient = 0.813) which indicated high reliability [55][56][57].…”
Section: Questionnaire Deployment and Data Collectionmentioning
confidence: 99%